Managerial Competencies Development of Oil Palm Plantation Managers for Industry 4.0 Era - Eksita Mariz Ramadhinta; Cahyadi, Eko Ruddy; Sukmawati, Anggraini (Jurnal Manajemen & Agribisnis, 2022)
This study aims to identify the level of difference between the required competency values and the current competency values for plantation managers and determine the priority criteria for the competency of oil palm plantation managers according to the needs of Industry 4.0. The research method used paired sample z test and Analytical Hierarchy Process (AHP). Paired sample z test to determine the significance of the independent variable and the dependent variable. The results using the paired sample z test, that the current average value for soft competency is lower than the required value. Hence, the current average value for soft competency needs to be increased. The results using AHP obtained the priority from the criteria elements, namely social skills, then cognitive abilities, and system skills. Each of the priority elements of the criteria for social skills, cognitive abilities, and systems skills consists of training and coaching employees, responsibilities as well as judgment and decision making. Industry 4.0's approach to social skills resulted in long-distance communication by implementing digitalization. The implementation of cognitive factors as knowledge can encourage innovation and creativity. While system skills, facilitate the process of repetitive activities become quickly done so as to save time. Keywords: analytical hierarchy process, competency level index, competency model, hard skills, soft skills